A Systematic Literature Review of Merit-based Personnel Mutation Systems: Implementation Challenges in the South Sulawesi Regional Police - Suryawan, Arief Doddy; Ibrahim, Muh. Akmal; Hasniati, ‎; Pauzi, Rizal (KnE Social Sciences, 2025)
This research examines the implementation of a merit-based system with multi-level selection in the personnel mutation process at the South Sulawesi Regional Police through a systematic literature review (SLR) approach. The study employs a rigorous qualitative methodology following the PRISMA guidelines for systematic reviews, including comprehensive document identification, screening, eligibility assessment, and inclusion processes. A total of 40 documents spanning the period 2010 to 2025 were analyzed, comprising 26 peer-reviewed articles and 11 legal references, including government regulations, institutional policies, and official directives related to merit-based personnel systems in law enforcement institutions, and the analysis was further supplemented by threesupporting documents. Document analysis techniques were applied to critically evaluate relevant regulations and implementation practices, with coding schemes developed to identify key themes and patterns. The analysis reveals that while comprehensive regulations exist establishing merit principles, actual implementation remains constrained by limited assessment methodologies, inadequate integration between career development and mutation systems, and persistent traditional practices. The multi-level selection process demonstrates inconsistent application across different ranks, with more rigorous implementation at higher levels. The research also identifies unique challenges related to South Sulawesi’s geographical diversity and socio-cultural context, which require special consideration in competency frameworks. Additionally, organizational factors, including administrative procedures, information management systems, resource allocation, and institutional culture, significantly influence merit-based implementation. Based on these findings, the study recommends developing standardized competency assessment tools, strengthening Career Consideration Boards, enhancing information management systems, and integrating regional considerations into competency frameworks. The research contributes to theoretical understanding of merit-based implementation in law enforcement institutions and provides practical guidance for strengthening human resource management in the Indonesian National Police, particularly in regional contexts with distinctive geographical and socio-cultural characteristics.